2009
DOI: 10.5951/mt.103.2.0140
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Research to Teaching: Visual and Analytic Thinking in Calculus

Abstract: A frequent message in mathematics education focuses on the benefits of multiple representations of mathematical concepts (Aspinwall and Shaw 2002). The National Council of Teachers of Mathematics, for instance, claims that “different representations support different ways of thinking about and manipulating mathematical objects” (NCTM 2000, p. 360). A recommendation conveyed in the ongoing calculus reform movement is that students should use multiple representations and make connections among them so that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…Though a graphic representation was used to present the calculus problems, students translated the problems into algebraic representation based on their preferences for solution method, according to the researchers. Similar to the findings of Haciomeroglu et al, (2009), this study also concluded that both visual and verbal solution methods are essential components for successful mathematical performance. They emphasized the need in both modes of thinking-verbal and visual-to deepen students' understanding.…”
Section: Preferences and Mathematical Performancesupporting
confidence: 82%
See 1 more Smart Citation
“…Though a graphic representation was used to present the calculus problems, students translated the problems into algebraic representation based on their preferences for solution method, according to the researchers. Similar to the findings of Haciomeroglu et al, (2009), this study also concluded that both visual and verbal solution methods are essential components for successful mathematical performance. They emphasized the need in both modes of thinking-verbal and visual-to deepen students' understanding.…”
Section: Preferences and Mathematical Performancesupporting
confidence: 82%
“…However, students got incorrect answer if they tend to utilize one solution methods more over the other solution methods or vice versa. Haciomeroglu, Aspinwall, and Presmeg (2009) conducted an empirical case study for calculus students to explore the relationship between preference for solution methods and calculus performance. Rather than using the verbal representation of MPI, the researchers used graphic representations to present the derivative problems.…”
Section: Preferences and Mathematical Performancementioning
confidence: 99%
“…Objek yang abstrak inilah yang menjadi penyebab matematika serasa pelajaran yang susah untuk di pelajari. Apabila pembelajarannya kurang atau tanpa menggunakan media alat bantu pengajaran, maka pembelajarannya akan menjadi abstrak (Haciomeroglu et al, 2009). Maka dari itu pentingnya strategi dalam pembelajaran, salah satunya yaitu menggunakan model pembelajaran yang tepat dengan bantuan media alat peraga.…”
unclassified